Effects of Three Anesthesia Methods on Inflammation, Oxidative Stress, Analgesia and Cognition in Elderly Patients Receiving Hip Replacement: Effects of Anesthesia on Inflammation, Oxidative Stress and Analgesia - Zhang, Jizheng; Sun, Xiaohua; Liu, Yan; Gui, Xiaochen; Ren, Wanlu (Cellular and Molecular Biology, 2022)
The study aimed to investigate the effects of different anesthesia methods on the analgesia, inflammation and oxidative stress levels and cognitive function in elderly patients undergoing hip replacement. 100 elderly patients requiring hip replacement and admitted to Tianjin Hospital from March 2017 to March 2019 were enrolled and divided into group A (n=35, general anesthesia with endotracheal intubation), group B (n=35, epidural anesthesia) and group C (n=30, general anesthesia with endotracheal intubation + epidural anesthesia). The basic vital signs, inflammatory factors, stress response indicators and cognitive function changes were compared among three groups. Additionally, the effects of three different anesthesia methods were analyzed based on the differences in postoperative analgesic effect, extubation time and recovery time. The vital signs [systolic blood pressure (SBP), diastolic blood pressure (DBP) and heart rate (HR)] were lower in group C than those in group A and group B after surgery (p<0.05). The VAS score at 12 h and 24 h after surgery was lower than that at 3 h after surgery (p<0.05). Group A and B had increased levels of these inflammatory factors after surgery compared with those before surgery. Postoperative extubation time, eye-opening time upon calling and recovery time were significantly shorter in group C than those in groups A and B (p<0.05). The oxidative stress indexes in group C were remarkably lower than those in groups A and B (p<0.05). The MMSE score was decreased in groups A and B after surgery compared with that before surgery (p<0.05). General anesthesia combined with epidural anesthesia applied in elderly patients undergoing hip replacement achieves a good anesthetic effect and is able to stabilize the vital signs and stress levels of patients and improve postoperative analgesic effect and cognitive function, which is worthy of popularization in clinical practice.